The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1080/01446193.2021.1901950
|View full text |Cite
|
Sign up to set email alerts
|

The value of incremental environmental sustainability innovation in the construction industry: an event study

Abstract: Investment in the innovation of environmental sustainability in construction has been encouraged due to the industry's resource-intensity. However, it remains unclear how to convince shareholders and construction companies to invest in environmental innovations.This research used the event study method with a sample of 129 announcements in the construction industry from 2011 to 2017 to investigate the relationship between incremental environmental sustainability innovation and the stock market reactions of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 114 publications
0
5
0
Order By: Relevance
“…Natural resources play a key role in some firms’ strategic decisions (Hart, 1995) and in their centrality to several SDGs that challenge firms to make bold changes in their use of such finite resources (Bringezu & Bleischwitz, 2017; UN, 2015b; United Nations Environment Program, 2011). For example, Duong and colleagues’ (2021) recent analysis on the construction sector underscores the urgency of transforming high resource-intensive industries into more sustainable ones; a call that is shared by a number of other scholars (e.g., Kajander et al, 2012; Tan et al, 2015). Other recent studies have singled out firms in natural resource-intensive sectors for study, in part due to the scrutiny placed on major emitters of greenhouse gases (e.g., Cho et al, 2018; Talbot & Borial, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Natural resources play a key role in some firms’ strategic decisions (Hart, 1995) and in their centrality to several SDGs that challenge firms to make bold changes in their use of such finite resources (Bringezu & Bleischwitz, 2017; UN, 2015b; United Nations Environment Program, 2011). For example, Duong and colleagues’ (2021) recent analysis on the construction sector underscores the urgency of transforming high resource-intensive industries into more sustainable ones; a call that is shared by a number of other scholars (e.g., Kajander et al, 2012; Tan et al, 2015). Other recent studies have singled out firms in natural resource-intensive sectors for study, in part due to the scrutiny placed on major emitters of greenhouse gases (e.g., Cho et al, 2018; Talbot & Borial, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The emergence of strategic alliances is a consequence of global economic integration, manifested through voluntary cooperation agreements between two or more companies (Duong et al, 2021; Lin & Darnall, 2010). These agreements empower participating companies to attain objectives that an individual entity could not achieve solely due to its restricted capabilities (Ferreira, Coelho, & Moutinho, 2021; Kohtamäki et al, 2018).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Such an analysis could be applied as a part of methodology for developing the means for supporting the Green Deal objectives. The study of Duong et al (2021) [70] revealed that there is a positive stock market reaction to incremental sustainability innovation; however, there is a lack of studies that focus on the analysis of the investor behaviour in the context of changes in the market.…”
Section: The Background Of the Researchmentioning
confidence: 99%